A SEMIOTIC SIGNS ANALYSIS FOUND IN HOTEL TRANSYLVANIA: TRANSFORMANIA MOVIE POSTER - Kevin Octavia; Sujana Sujana (Journal of Language and Literature, 2022)
Semiotics is a study that explains signs, and that all things in this world are signs. Even if some things have no inherent significance, we can infuse meaning into them to make them signs. This research aims to find the meaning of semiotic signs found in the Hotel Transylvania: Transformania movie poster using the trichotomy signs theory based on Charles Sanders Peirce’s. The source data in this research is the Hotel Transylvania: Transformania movie poster. Then, the data studied are to explain the meaning of the trichotomy signs, categorize the verbal and non-verbal signs, and understand the color concept. A descriptive-qualitative method was applied in the analysis of this research. The result of the research shows that there are 97 data. In the representamen, there are 22 data: qualisign 1 data, sinsign 14 data, and legisign 7 data. In the object, there are 38 data: icon 14 data, index 9 data, and symbol 15 data. And for the interpretant, there are 37 data: rheme 29 data, dicent sign 1 data, and argument 7 data. Furthermore, for the verbal signs, there are 7 data, and for the non-verbal signs, there are 90 data.